The Transformation Model of Islamic Boarding Schools as an Incubator for Sharia Entrepreneurship in the Digital Economy Era - Nurlaili Janati; Delima Afriyanti; Siti Nurdinah; Ruri Liana Anugrah; Rini Ariyanti (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to examine the transformation of pesantren education in promoting sharia-based entrepreneurship through a vocational education approach at the Riau Technology Islamic Boarding School. In facing the challenges of the Industrial Revolution 5.0, Islamic boarding schools are required not only to produce graduates who are spiritually religious but also technically and economically competent. This study uses a qualitative approach using the case study method, where data is collected through observation, in-depth interviews, and documentation. The findings of the study show that the integration of the vocational curriculum with Islamic values can shape the character of students as independent and ethical young entrepreneurs. The Sharia-based business unit managed by students serves as a real-world learning platform that not only hone skills but also instill Islamic trading principles. These findings show that the Islamic boarding school-based vocational education model has significant replication potential in other Islamic education contexts. This study recommends strengthening the curriculum, strategic partnerships, digitizing learning, and business mentoring for students as a further step in developing sharia entrepreneurship in the pesantren environment.